Intraoperative device closure of perimembranous ventricular septal defects in the young children under transthoracic echocardiographic guidance; initial experience - Cao, Hua (BioMed Central, 2011)
OBJECTIVES: This study aimed to assess the safety and feasibility of intraoperative device closure of perimembranous ventricular septal defects (VSD) in young children guided by transthoracic echocardiography (TTE). METHODS: We enrolled 18 patients from our hospital to participate in the study from June 2011 to September 2011. A minimal inferior median incision was performed after full evaluation of the perimembranous VSD by real-time TTE, and a domestically made device was inserted to occlude the perimembranous VSD. The proper size of the device was determined by means of transthoracic echocardiographic analysis. RESULTS: Implantation was ultimately successful in 16 patients using TTE guidance. In these cases, the complete closure rate immediately following the operation and on subsequent follow-up was 100%. Symmetric devices were used in 14 patients, and asymmetric devices were used in two patients. Two patient were transformed to surgical treatment, one for significant residual shunting, and the other for unsuccessful wire penetration of the VSD. The follow-up periods were less than nine months, and only one patient had mild aortic regurgitation. There were no instances of residual shunt, noticeable aortic regurgitation, significant arrhythmia, thrombosis, or device failure. CONCLUSIONS: Minimally invasive transthoracic device closure of perimembranous VSDs is safe and feasible, using a domestically made device under transthoracic echocardiographic guidance, without the need for cardiopulmonary bypass. This technique should be considered an acceptable alternative to surgery or device closure guided by transesophageal echocardiography in selected young children. However, a long-term evaluation of outcomes is necessary.